Enhanced Photocatalytic Degradation of Methylene Blue Dye Using Co3O4 Nanoparticles from the Fruit Extracts of Diplocyclos palmatus (L) C. Jeffrey for Wastewater Remediation - Parethe Gurusamy Thangam; Rajesh Pattulingam; Velmani Vellaiyan; Balaji Murugaesan; Kavica Sathasivam (Journal of Water and Environmental Nanotechnology)
Effective and reliable nanoparticles are needed for degrading organic dyes. In this present study, Cobalt oxide (Co3O4) nanoparticles, have been synthesized by Co-precipitation technique and assessed as optimized catalyst for photocatalytic dye degradation under sunlight irradiation. The nanoparticles were characterized for UV- visible light spectra, XRD analysis, Scanning electron microscopy (SEM) and energy - dispersive X-ray (EDX) spectroscopy showing their irregular, small particles with stakes of various sizes. From EDX spectra, the elemental composition of nanoparticles resulting their presence in oxide form. In an aqueous medium, the degradation of methylene blue (MB) dye under sunlight irradiation using this metal oxide nanoparticles as photocatalyst. The study evaluated the influence of various impacts, such as dye concentration, irradiation time, pH medium, various dosages of catalyst and recovered catalyst dosage. The results concluded that Co3O4 nanoparticles showed high activity of photocatalytic dye degradation, degrading 91% of dye in 120 min. Increased degradation of dye achieved on longer irradiation time. 93% degradation achieved at pH 9 in 120 min, resulting enhanced dye degradation obtained on increasing the medium of the pH. Moreover, increased dye concentration results in decreased photodegradation. Using 0.013g of photocatalyst 92% of dye was degraded showing that higher catalyst dosage results in higher degradation of dye. On recovering the catalyst, 81%, of dye degraded during cycle 4. Thus, the Co3O4 nanoparticles exhibited consistent visible-light responsive activity as a photocatalyst in degrading organic pollutants for wastewater remediation.